CURRENT PROBLEMS OF TEACHING OF PATHOPHYSIO-LOGY FOR FOREIGN STUDENTS AND THEIR DECISION - Rykalo, N.A. (World of Medicine and Biology, 2013)
This article presents the experience and the current problems of teaching pathophysiology, as a fundamental discipline for foreign students. We discuss decision based on our multiyear of experience teaching.
Keywords: pathophysiology; feature of teaching; foreign-students